AN ANALYSIS OF THE EFFECTS OF RISK MANAGEMENT PROCESSES ON SUPPLY CHAIN PERFORMANCE IN THE INSURANCE INDUSTRY IN KENYA (A CASE OF KENYA REINSURANCE CORPORATION LIMITED) - SIGILAI, JENIFFER CHEPKOECH (IJRDO - Journal of Business Management, 2015)
Risk Management is defined in the standard (AS/NZS 4360:2004) as the systematic applicationof management policies, procedures and practices to the tasks of establishing the context,identifying, analysing, assessing, treating, monitoring and communicating. This study sought tofind out the effects of risk management process on supply chain performance in insuranceindustry having Kenya Re as its case study. The main factors that was examined include;monitoring, business planning, resource allocation and risk reduction. The methodology of thisstudy was purely qualitative. The study adopted stratified sampling to pick the respondents froma target population of 105 employees at the Kenya Re, Nairobi office. Data was obtainedthrough primary data sources by means of face to face interviews guided by questionnairesadministered to a selected sample. A total of 32 employees sampled from different departmentsformed the respondents of this study. The questionnaires was administered through drop andpick later method to the respondents. Once collected, the data was presented using tables andfigures. Findings from the study revealed that the highest predictor for Supply ChainPerformance is Risk Resource allocation with a beta value of 0.635 followed by Risk Planningwith a beta value of 0.548 then Risk Reduction with a beta value of 0.355. Risk Monitoring is theleast predictor of Supply Chain Performance with a beta value of 0.323. The study concludesthat risk planning is very essential in supply chain performance since it reduces possible supplychain risks. This is bearing in mind that results from monitoring should be used in controls the study also concludes that risk planning indeed reduces disruptions in supply chain and thusmitigates risks in the supply chain which is an essential variable in supply chain performance.The study recommends that In order to ensure that the resources allocation process is efficient;the players in the insurance industry should engage a broad range of stakeholders in order toensure that the process is reasonable and they are accountable. The study recommends furtherresearch on the compatibility of risk management and business process management, includingthe ability to minimize risks in business processes by design and to mitigate such risks at runtime.